BRIDGING THE GAP BETWEEN STRATEGIC TARGETS AND OPERATIONAL FEASIBILITY: AHP-BASED KPI OPTIMIZATION IN PT BUKIT ASAM TBK - Bagus Budianto; Dermawan Wibisono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to bridge the gap between PT Bukit Asam Tbk's strategic targets and its operational feasibility by optimizing Key Performance Indicators (KPIs) within the company’s Balanced Scorecard (BSC). Using the Analytic Hierarchy Process (AHP), this research prioritizes internal perceptions of KPI importance across the four BSC perspectives: Financial & Market, Customer Focus, Internal Business Process, and Learning & Growth. Interviews and AHP-based pairwise comparisons reveal that several KPIs currently in use do not reflect PTBA’s internal strategic priorities. Additionally, the Traffic Light System (TLS) is introduced to assess performance realization and validate the feasibility of target setting. The results suggest that the most favored alternative is refining KPI targets rather than changing its components or weight. This approach not only improves alignment between internal and external expectations but also enables more realistic and measurable performance evaluation. The findings are expected to serve as a foundation for PTBA’s strategic dialogue with MIND ID and for broader KPI governance improvements.